Aspirin reduces the mortality risk of patients with community-acquired pneumonia: a retrospective propensity-matched analysis of the MIMIC-IV database - Wang, Guangdong; Sun, Jiaolin; Zhang, Yaxin; Wang, Na; Liu, Tingting; Ji, Wenwen; Lv, Lin; Yu, Xiaohui; Cheng, Xue; Li, Mengchong; Hu, Tinghua; Shi, Zhihong (Frontiers in Pharmacology, 2024)
Background: Community-acquired pneumonia (CAP) is a common infectious disease characterized by inflammation of the lung parenchyma in individuals who have not recently been hospitalized. It remains a significant cause of morbidity and mortality worldwide. Aspirin is a widely used drug, often administered to CAP patients.However, the benefits of aspirin remain controversial.Objective: We sought to determine whether aspirin treatment has a protective effect on the outcomes of CAP patients.: We selected patients with CAP from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. Propensity score matching (PSM) balanced baseline differences. A multivariate Cox regression model assessed the relationship between aspirin treatment and 28-day mortality.Results: A total of 3,595 patients were included, with 2,261 receiving aspirin and 1,334 not. After PSM, 1,219 pairs were matched. The 28-day mortality rate for aspirin users was 20.46%, lower than non-users. Multivariate Cox regression indicated aspirin use was associated with decreased 28-day mortality (HR 0.75, 95% CI 0.63-0.88, p < 0.001). No significant differences were found between 325 mg/day and 81 mg/day aspirin treatments in terms of 28-day mortality, hospital mortality, 90-day mortality, gastrointestinal hemorrhage, and thrombocytopenia. However, intensive care unit (ICU) stay was longer for the 325 mg/day group compared to the 81 mg/day group (4.22 vs. 3.57 days, p = 0.031).Aspirin is associated with reduced 28-day mortality in CAP patients.However, 325 mg/day aspirin does not provide extra benefits over 81 mg/day and may lead to longer ICU stays.